2022
DOI: 10.1177/10775595221104829
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotemporal Invitations: 6- to 9-year-Old Maltreated Children’s Tendency to Misinterpret Invitations Referencing “Time” as Solely Requesting Conventional Temporal Information

Abstract: Forensic interviewers ask children broad input-free recall questions about individual episodes in order to elicit complete narratives, often asking about “the first time,” “the last time,” and “one time.” An overlooked problem is that the word “time” is potentially ambiguous, referring both to a particular episode and to conventional temporal information. We examined 191 6-9-year-old maltreated children’s responses to questions about recent events varying the wording of the invitations, either asking children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Furthermore, adults reported that about the time invitations could be asked of younger witnesses than what happened invitations. This was surprising, given that what happened invitations are thought to be the optimal form of the question and have been repeatedly shown to be less likely to lead to pseudotemporal responses (Friend et al, 2022; McWilliams et al, 2023). Unfortunately, these findings may suggest that adults are failing to recognise the lack of clarity in about the time questions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, adults reported that about the time invitations could be asked of younger witnesses than what happened invitations. This was surprising, given that what happened invitations are thought to be the optimal form of the question and have been repeatedly shown to be less likely to lead to pseudotemporal responses (Friend et al, 2022; McWilliams et al, 2023). Unfortunately, these findings may suggest that adults are failing to recognise the lack of clarity in about the time questions.…”
Section: Discussionmentioning
confidence: 99%
“…‘Tell me about the last time you played soccer’) that include the word ‘time’, and thus may be misinterpreted as asking about the time rather than the event (e.g. ‘It was on Saturday.’; Friend et al, 2022; McWilliams et al, 2023). Invitations using the word ‘time’ are recommended by standardised interviewing protocols as a means of eliciting information about specific episodes (Sternberg et al, 2001; Zajac & Brown, 2018).…”
Section: Pseudotemporal Invitations: the Ambiguity Of Invitations Usi...mentioning
confidence: 99%
See 3 more Smart Citations